2022
DOI: 10.3389/fvets.2022.1006676
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of bovine mastitis-associated Staphylococcus aureus in China and its antimicrobial resistance rate: A meta-analysis

Abstract: In this study, to optimize the Staphylococcus aureus control program, a meta-analysis was conducted to investigate the epidemiology and antimicrobial resistance (AMR) profile of S. aureus-associated bovine mastitis in China from 2000 to 2020. A total of 33 publications from PubMed, Google Scholar, and China National Knowledge Infrastructure (CNKI) database were included in our research, among which nine publications included the AMR test. The pooled prevalence of S. aureus was 36.23%, and subgroup analysis rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
4
4
0
Order By: Relevance
“…In this study, most isolates were susceptible to ciprofloxacin, gentamicin, and chloramphenicol. These results correlate with a meta-analysis of bovineassociated S. aureus in China which reported that 63.8 %, 73.6 %, and 89.7 % S. aureus isolates were susceptible to quinolones, aminoglycosides, and phenicols, respectively (Wang et al, 2022). A study in Korea showed that 88.1 % S. aureus isolates were susceptible to gentamicin (Nam et al, 2011), while another study in Germany reported that 68.7 % MRSA isolates were susceptible to gentamicin (Fessler et al, 2010).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In this study, most isolates were susceptible to ciprofloxacin, gentamicin, and chloramphenicol. These results correlate with a meta-analysis of bovineassociated S. aureus in China which reported that 63.8 %, 73.6 %, and 89.7 % S. aureus isolates were susceptible to quinolones, aminoglycosides, and phenicols, respectively (Wang et al, 2022). A study in Korea showed that 88.1 % S. aureus isolates were susceptible to gentamicin (Nam et al, 2011), while another study in Germany reported that 68.7 % MRSA isolates were susceptible to gentamicin (Fessler et al, 2010).…”
Section: Discussionsupporting
confidence: 82%
“…Bovine mastitis is one of the most common diseases affecting the quantity and quality of world milk production (Ruegg, 2017;Wang et al, 2022). Mastitis incurs various costs, including decreased milk production, condemnation of milk due to antibiotic residues, veterinary expenses, and culling of chronically infected cattle (Nurhayati and Martindah, 2015;Abebe et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…[ 67 ] reported in another investigation in Bulgaria, in which erythromycin resistance was identified in 7/12 (58%) samples. Additionally, our research is supported by a Chinese study that detected macrolide resistance in 34.08% of patients [ 68 ]. By contrast, Algammal et al .…”
Section: Discussionsupporting
confidence: 63%
“…An increase in AR to clindamycin, erythromycin, gentamycin and oxacillin was not observed, though it was reported to occur globally for S. aureus strains, causing bovine mastitis or isolated from milk and dairy products [ 35 , 36 ]. In addition, a recent meta-analysis carried out in China suggested how the AR rate can be particularly high in some geographical contexts, suggesting local misuse of antibiotics [ 37 ]. Therefore, it can be hypothesized that the low frequency of phenotypic AR for some antibiotic classes observed in this study is a consequence of the low usage of those drugs, as corroborated by veterinarian’s statements.…”
Section: Discussionmentioning
confidence: 99%